Housework and fiscal expansions - Stefano Gnocchi; Daniela Hauser; Evi Pappa (Bank of Canada, 2014)
We build an otherwise-standard business cycle model with housework, calibrated consistently with data on time use, in order to discipline consumption-hours complementarity and relate its strength to the size of fiscal multipliers. We show that if substitutability between home and market goods is calibrated on the empirically relevant range, consumption-hours complementarity is large and the model generates fiscal multipliers that agree with the evidence. Hence, our analysis supports the relevance of consumption-hours complementarity for fiscal multipliers. However, we also find that explicitly modeling the home sector is more appealing than restricting to the consumption-leisure margin and/or to the preferences proposed by Greenwood, Hercowitz and Huffman (1988). A housework model can imply substantial complementarity, without low wealth effects contradicting the microeconomic evidence. – – Nous construisons un modèle de cycle économique standard auquel nous intégrons les travaux ménagers, et que nous étalonnons en fonction de données sur l'emploi du temps, afin d'assujettir aux données la complémentarité entre la consommation et les heures travaillées et d'établir le lien entre le degré de cette complémentarité et la taille des multiplicateurs budgétaires. Nous montrons que, si la substituabilité entre les produits maison et les produits marchands est étalonnée sur la fourchette de données pertinente du point de vue empirique, la complémentarité consommation-heures travaillées est importante et le modèle génère des multiplicateurs budgétaires qui concordent avec les données. Ainsi, l'importance de la complémentarité consommation-heures travaillées pour les multiplicateurs budgétaires est étayée par notre analyse. Par ailleurs, nous constatons également qu'il est plus avantageux de modéliser explicitement la production domestique que de s'en tenir à l'arbitrage consommation-loisirs ou aux preferences proposées par Greenwood, Hercowitz et Huffman (1988). Un modèle de travaux ménagers peut générer une complémentarité considérable, sans que de faibles effets de richesse viennent contredire les observations microéconomiques.
Keywords: E24; E32; E52; E62; 330; Fiscal policy; Business fluctuations and cycles